Fixing belt, fixing device, and image forming apparatus
The fixing belt with intertwined fibrous carbon aggregates in the base and elastic layers addresses inefficiencies in heat transfer and durability, achieving improved thermal conductivity and extended service life by balancing carbon content and diameter proportions.
Patent Information
- Application Number
- JP2021088682
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-05-26
- Publication Date
- 2025-01-15
- Estimated Expiration
- 2041-05-26
AI Technical Summary
Existing fixing belts in image forming apparatuses using electrophotographic methods face issues with inefficient heat transfer and reduced service life due to the lack of intertwining between fibrous carbons in the base and elastic layers, leading to increased temperature and potential belt breakage.
The fixing belt is designed with a base layer and elastic layer containing aggregates of intertwined fibrous carbons, where the maximum diameter of these aggregates is limited to specific proportions relative to the layer thickness, and the content of intertwined and non-intertwined fibrous carbons is balanced to enhance thermal conductivity and reduce torque, thereby improving heat transfer and durability.
This design results in a fixing belt with enhanced thermal conductivity and reduced torque, leading to a longer service life and reduced risk of belt breakage, ensuring stable operation during continuous paper feeding.
Smart Images

Figure 0007613271000003 
Figure 0007613271000004 
Figure 0007613271000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a fixing belt, a fixing device, and an image forming apparatus. [Background technology]
[0002] 2. Description of the Related Art In image forming apparatuses (such as copiers, facsimiles, and printers) using an electrophotographic method, a fixing belt is used to fix a toner image formed on a recording medium onto the recording medium.
[0003] Patent Document 1 discloses a functional membrane containing aggregates of entangled carbon nanotubes, each having a diameter of 50 μm or less, a height of less than 5 μm, and a ratio of the height to the diameter (height / diameter) of less than 0.1. Moreover, Patent Document 1 discloses a polyimide tube obtained by dispersing carbon nanotubes as needle-like highly thermally conductive fillers in a polyimide resin. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2019-140105 A [Patent Document 2] JP 2011-186127 A Summary of the Invention [Problem to be solved by the invention]
[0005] An object of the present disclosure is to provide a fixing belt that can be applied to a fixing method in which a heat source is present inside the fixing belt and heat from the heat source is transferred to a toner image via the fixing belt, and that can achieve a longer life, compared to a case in which the base material layer and the elastic layer contain only unentangled fibrous carbon as fibrous carbon, or contain aggregates formed by multiple entangled fibrous carbons and the maximum diameter of such aggregates does not satisfy the following relationship: [Means for solving the problem]
[0006] Specific means for solving the above problems include the following aspects. <1> The sheet has a base layer including a resin, an elastic layer including an elastic material, and a release layer in this order, The base material layer and the elastic layer each further include an aggregate formed by a plurality of fibrous carbons entangled with each other, the maximum diameter of the aggregate in the base layer is 50% or less of the thickness of the base layer; A fixing belt, wherein the maximum diameter of the aggregate in the elastic layer is 15% or less of the thickness of the elastic layer.
[0007] <2> The base layer and the elastic layer each further contain fibrous carbon that is not entangled with each other. <1> The fixing belt according to claim 1. <3> In the base material layer and the elastic layer, the content A of the aggregate and the content B of the fibrous carbon that are not entangled with each other satisfy the relationship A≧B on a mass basis, <2> The fixing belt according to claim 1. <4> The base material layer and the elastic layer each have a ratio (A / (A+B)) of the content A of the aggregate to the total amount of the content A of the aggregate and the content B of the fibrous carbon that is not entangled with each other, of 0.50 or more and 0.95 or less on a mass basis. <2> or <3> The fixing belt according to claim 1. <5> The content A1 of the aggregate contained in the base material layer is 0.1 mass% or more and 20 mass% or less with respect to the total mass of the base material layer. <1> ~ <4> 13. The fixing belt according to claim 12, <6> The content A2 of the aggregate contained in the elastic layer is 0.1 mass% or more and 40 mass% or less with respect to the total mass of the elastic layer. <1> ~ <5> The fixing belt according to claim 1. <7> a content A1 of the aggregate contained in the base layer and a total mass A2 of the aggregate contained in the elastic layer satisfy the relationship A1≦A2 on a mass basis; <1> ~ <4> 13. The fixing belt according to claim 12, <8> The content A1 of the aggregate is 0.1 mass% or more and 20 mass% or less with respect to the total mass of the base material layer, and the content A2 of the aggregate is 0.1 mass% or more and 40 mass% or less with respect to the total mass of the elastic layer. <7> The fixing belt according to claim 1. <9> The fibrous carbon is a carbon nanotube. <1> ~ <8> 13. The fixing belt according to claim 12,
[0008] <10> A first rotating body and a second rotating body arranged in contact with an outer surface of the first rotating body, At least one of the first rotating body and the second rotating body, <1> ~ <9> 2. The fixing belt according to claim 1 , a fixing device that fixes a toner image formed on a surface of the recording medium by inserting the recording medium through a contact portion between the first rotating body and the second rotating body; <11> An image carrier; a charging means for charging the surface of the image carrier; an electrostatic latent image forming means for forming an electrostatic latent image on the charged surface of the image carrier; a developing unit for developing the electrostatic latent image formed on the surface of the image carrier with a developer containing a toner to form a toner image; a transfer means for transferring the toner image onto a surface of a recording medium; fixing the toner image onto the recording medium; <10> A fixing means comprising the fixing device according to claim 1, An image forming apparatus comprising: Effect of the Invention
[0009] <1> According to the invention, a fixing belt is provided that is applicable to a fixing method in which a heat source is present inside the fixing belt and heat from the heat source is transferred to a toner image via the fixing belt, and that can achieve a longer life, compared to a case in which the base material layer and the elastic layer contain only unentangled fibrous carbon as fibrous carbon, or contain aggregates formed by multiple entangled fibrous carbons and the maximum diameter of such aggregates does not satisfy the above relationship. According to the invention according to <2>, there is provided a fixing belt including an aggregate in which a plurality of fibrous carbons are intertwined with each other, and capable of achieving a longer service life as compared with a case where no fibrous carbon that is not intertwined with each other is included. According to the invention according to <3>, there is provided a fixing belt capable of achieving a longer service life as compared with a case where the content A of the aggregate and the content B of the fibrous carbon that is not intertwined with each other satisfy the relationship of A < B on a mass basis. According to the invention according to <4>, there is provided a fixing belt capable of achieving a longer service life as compared with a case where the ratio (A / (A + B)) is less than 0.50 or more than 0.95 on a mass basis. According to the invention according to <5>, there is provided a fixing belt capable of achieving a longer service life as compared with a case where the content A1 of the aggregate contained in the base material layer is more than 20% by mass with respect to the total mass of the base material layer. According to the invention according to <6>, there is provided a fixing belt capable of achieving a longer service life as compared with a case where the content A2 of the aggregate contained in the elastic layer is more than 40% by mass with respect to the total mass of the elastic layer. According to the invention according to <7> or <8>, there is provided a fixing belt capable of achieving a longer service life as compared with a case where the content A1 of the aggregate contained in the base material layer and the total mass A2 of the aggregate contained in the elastic layer satisfy the relationship of A1 > A2 on a mass basis. According to the invention according to <9>, there is provided a fixing belt capable of achieving a longer service life as compared with a case where the fibrous carbon is not a carbon nanotube.
[0010] According to the invention according to <10> or <11>, when the base material layer and the elastic layer include only fibrous carbon that is not intertwined with each other as the fibrous carbon, or include an aggregate in which a plurality of fibrous carbons are intertwined with each other, and the maximum diameter of such an aggregate does not satisfy the above relationship, there is provided a fixing device or an image forming device including a fixing belt, which is applied to a fixing method in which a heat source exists inside the fixing belt and heat from the heat source is transmitted to a toner image through the fixing belt, and capable of achieving a longer service life.
Brief Description of the Drawings
[0011] [Figure 1]1 is a schematic cross-sectional view illustrating an example of a fixing belt according to the present disclosure. [Diagram 2] 1 is a schematic configuration diagram illustrating an example of an embodiment of a fixing device according to the present disclosure. [Diagram 3] 1 is a schematic configuration diagram illustrating an example of an embodiment of an image forming apparatus according to the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, embodiments of the present invention will be described. These descriptions and examples are merely illustrative of the embodiments, and are not intended to limit the scope of the embodiments.
[0013] In the present specification, in which numerical ranges are described in stages, the upper limit or lower limit value described in one numerical range may be replaced with the upper limit or lower limit value of another numerical range described in stages. In addition, in the numerical ranges described in this specification, the upper or lower limit of the numerical ranges may be replaced with values shown in the examples.
[0014] In this specification, each component may contain multiple corresponding substances. In this specification, when referring to the amount of each component in a composition, if multiple substances corresponding to each component are present in the composition, the amount refers to the total amount of those multiple substances present in the composition, unless otherwise specified.
[0015] <Fixing belt> The fixing belt according to the present disclosure has, in that order, a base material layer containing a resin, an elastic layer containing an elastic material, and a release layer, wherein the base material layer and the elastic layer each further contain an aggregate formed by a plurality of fibrous carbons entangled with each other, and the maximum diameter of the aggregate in the base material layer is 50% or less of the thickness of the base material layer, and the maximum diameter of the aggregate in the elastic layer is 40% or less of the thickness of the elastic layer. Hereinafter, an aggregate formed by a plurality of fibrous carbons entangled with one another will also be referred to as a specific aggregate, as appropriate.
[0016] As the fixing belt, for example, there is a fixing belt that is applied to a fixing method in which a heat source is present inside the fixing belt and heat from the heat source is transferred to a toner image via the fixing belt. In the fixing belt applied to such a fixing method, the base layer and the elastic layer each often contain a heat conductive material. However, if the heat transfer at the interface between the base layer and the elastic layer is inefficient, the temperature of the heat source that heats the fixing belt may become high when the fixing belt is heated to a set fixing temperature. If the temperature of the heat source becomes high, the deterioration of the lubricant present between the heat source and the fixing belt may be accelerated, and the belt may break due to an increase in torque.
[0017] In the fixing belt according to the present disclosure, both the base material layer and the elastic layer contain, as a conductive material, aggregates (i.e., specific aggregates) formed by a plurality of fibrous carbons intertwined with each other. At the interface between the base material layer and the elastic layer each containing the specific aggregates, the contact area between the specific aggregates becomes large due to the shape of the specific aggregates, and therefore, it is considered that heat transfer becomes smoother than when the fibrous carbons not intertwined with each other are contained. Therefore, in the fixing belt according to the present disclosure, when the fixing belt is heated to a set fixing temperature, the temperature of the heat source that heats the fixing belt is prevented from becoming too high, and belt breakage is suppressed, thereby presumably achieving a longer life. In addition, since the fixing belt according to the present disclosure allows smooth transfer of heat at the interface between the base material layer and the elastic layer as described above, the fixing belt can be preferably applied to a fixing method in which a heat source is present inside the fixing belt and heat from the heat source is transferred to a toner image via the fixing belt.
[0018] The fixing belt according to the present disclosure will be described with reference to FIG. FIG. 1 is a schematic cross-sectional view showing an example of a fixing belt according to the present disclosure. The fixing belt 110 shown in FIG. 1 has a base layer 110A, an elastic layer 110B provided on the base layer 110A, and a release layer 110C provided on the elastic layer 110B. The layer structure of fixing belt 110 according to the present disclosure is not limited to the layer structure shown in FIG. 1, and may be a layer structure in which an adhesive layer is interposed between elastic layer 110B and release layer 110C.
[0019] The components of the fixing belt according to the present disclosure will be described in detail below, with the reference numerals omitted.
[0020] [Base material layer] The base layer of the fixing belt according to the present disclosure includes a resin and an aggregate (that is, a specific aggregate) formed by a plurality of fibrous carbons entangled with one another. The maximum diameter of the specific aggregate in the base layer is 50% or less of the base layer thickness.
[0021] [Specific aggregate] The specific aggregate in the base layer is used as a heat conducting material. As described above, the maximum diameter of the specific aggregates in the base layer is 50% or less of the base layer thickness, preferably 40% or less, and more preferably 25% or less, while the maximum diameter of the specific aggregates is more preferably 1% or more of the base layer thickness.
[0022] In addition, from the viewpoint of smooth heat transfer at the interface between the base layer and the elastic layer, the maximum diameter of the specific aggregates in the base layer is preferably 0.5 μm or more and 60 μm or less, more preferably 1 μm or more and 40 μm or less, and even more preferably 3 μm or more and 25 μm or less.
[0023] The specific aggregate in the base layer is an aggregate formed by entangling a plurality of fibrous carbons with each other, and may have any shape as long as it has the above-mentioned maximum diameter. The specific aggregate in the belt may be, for example, spherical, elliptical, or irregular.
[0024] In addition, from the viewpoint of smooth heat transfer at the interface between the base layer and the elastic layer, the ratio of the minor axis Y to the major axis X of the specific aggregate in the base layer (minor axis Y / major axis X) is preferably 0.1 or more and 1 or less, more preferably 0.1 or more and 0.8 or less, and even more preferably 0.2 or more and 0.6 or less.
[0025] The maximum diameter, major axis X, and minor axis Y of a particular aggregate are measured in the following manner. The release layer and the elastic layer are peeled off from the fixing belt, and the surface of the exposed base layer is measured using a SEM (scanning electron microscope) image. The longitudinal length and the normal length of any 10 specific aggregates exposed on the surface are measured, and the arithmetic average values of the maximum diameter (= major axis X) and the minor axis Y of each of the 10 specific aggregates are determined. The release layer and the elastic layer may be peeled off from the fixing belt by, for example, the same method as that used for measuring the thermal conductivity, which will be described later.
[0026] The length of the fibrous carbon contained in the specific aggregate in the base layer is preferably 0.5 μm or more and 100 μm or less, more preferably 2 μm or more and 80 μm or less, and even more preferably 3 μm or more and 60 μm or less.
[0027] The diameter of the fibrous carbon contained in the specific aggregate in the base layer is preferably 20 nm or more and 300 nm or less, more preferably 25 nm or more and 250 nm or less, and further preferably 30 nm or more and 200 nm or less.
[0028] The length and diameter of the fibrous carbon contained in the specific aggregate are measured by the following method. The release layer and the elastic layer are peeled off from the fixing belt, and the surface of the exposed base layer is measured using an SEM image. The length and diameter (thickness) of 10 arbitrary carbon fibers from the specific aggregate exposed on the surface are measured, and the arithmetic average values of the 10 carbon fibers are taken as the length and diameter values. The release layer and the elastic layer may be peeled off from the fixing belt by, for example, the same method as that used for measuring the thermal conductivity, which will be described later.
[0029] The number of fibrous carbons contained in the specific aggregate is not particularly limited as long as it is a plurality (that is, two or more).
[0030] The fibrous carbon contained in the specific polymer in the substrate layer is preferably a carbon nanotube from the viewpoints of availability, thermal conductivity, and the like.
[0031] From the viewpoint of smoother heat transfer at the interface between the base layer and the elastic layer, the content A1 of the specific aggregate in the base layer is preferably 0.1 mass % or more and 20 mass % or less, more preferably 1 mass % or more and 18 mass % or less, even more preferably 2 mass % or more and 15 mass % or less, and particularly preferably 5 mass % or more and 15 mass % or less, relative to the total mass of the base layer.
[0032] [Disjointed fibrous carbon] From the viewpoint of further increasing thermal conductivity, the base layer preferably contains non-entangled fibrous carbon in addition to the specific aggregates described above. That is, the base layer preferably contains a resin, specific aggregates, and fibrous carbon that is not entangled with one another.
[0033] In the base layer, the length of the non-entangled fibrous carbon is preferably 1 μm or more and 100 μm or less, more preferably 2 μm or more and 80 μm or less, and even more preferably 3 μm or more and 60 μm or less.
[0034] In the base layer, the diameter of the non-entangled fibrous carbon is preferably 20 nm or more and 300 nm or less, more preferably 25 nm or more and 250 nm or less, and further preferably 30 nm or more and 200 nm or less.
[0035] In addition, in the base material layer, the fibrous carbon that is not entangled with each other may be the same as or different from the fibrous carbon contained in the specific aggregate (i.e., the fibrous carbon that constitutes the specific aggregate).
[0036] In the base layer, the non-entangled fibrous carbon is preferably carbon nanotubes from the viewpoints of availability, thermal conductivity, and the like.
[0037] When the base layer contains non-entangled fibrous carbon, the content thereof is preferably more than 0 mass% and not more than 15 mass%, more preferably 0.5 mass% or more and 10 mass% or less, even more preferably 1 mass% or more and 10 mass% or less, and particularly preferably 1 mass% or more and 5 mass% or less, relative to the total mass of the base layer.
[0038] From the viewpoint of increasing the thermal conductivity of the base material layer, it is preferable that the content A of the specific aggregates and the content B of the unentangled fibrous carbon satisfy the relationship A≧B on a mass basis. In addition, from the viewpoint of increasing the thermal conductivity of the base material layer, the ratio (A / (A+B)) of the content A of specific aggregates to the total amount of the content A of specific aggregates and the content B of unentangled fibrous carbon, on a mass basis, is preferably 0.50 or more and 0.95 or less, and more preferably 0.50 or more and 0.90 or less.
[0039] The content A of the specific aggregates and the content B of the non-entangled fibrous carbon are measured by the following method. The release layer and the elastic layer are peeled off from the fixing belt, and the surface SEM image of the exposed base layer is subjected to image analysis to measure. The total area of the specific aggregates and the total area of the fibrous carbon that is not entangled with each other are determined by image analysis of the surface SEM image. Here, the number of measurement samples (i.e., the number of SEM images to be image analyzed) is 5. The "content A of specific aggregates" is the arithmetic average value of the "total area of the specific aggregates in the surface area of the base layer" obtained by the above method for 5 samples, and the "content B of fibrous carbon that is not entangled with each other" is the arithmetic average value of the "total area of the fibrous carbon that is not entangled with each other in the surface area of the base layer" obtained by the above method for 5 samples. Then, the ratio (A / (A+B)) is calculated from the "content A of specific aggregates" and the "content B of fibrous carbon not entangled with each other" obtained as described above. When calculating the ratio (A / (A+B)), if the specific gravities of the specific aggregates and the fibrous carbon not entangled with each other are different, the contents A and B may be corrected using the respective specific gravities. The release layer and the elastic layer may be peeled off from the fixing belt by, for example, the same method as that used for measuring the thermal conductivity described later.
[0040] [resin] The resin contained in the base layer is preferably a heat-resistant resin. Examples of the resin include heat-resistant resins having high heat resistance and high strength, such as polyimide, aromatic polyamide, and liquid crystal materials such as thermotropic liquid crystal polymer. In addition to these, polyester, polyethylene terephthalate, polyethersulfone, polyether ketone, polysulfone, polyimide amide, etc. may be used. Among these, polyimide is preferred as the resin.
[0041] Examples of polyimides include imidized products of polyamic acids (precursors of polyimide resins), which are polymers of tetracarboxylic dianhydrides and diamine compounds.Specific examples of polyimides include resins obtained by polymerizing equimolar amounts of tetracarboxylic dianhydrides and diamine compounds in a solvent to obtain a polyamic acid solution, and then imidizing the polyamic acid.
[0042] The tetracarboxylic dianhydride may be either an aromatic or aliphatic compound, but from the viewpoint of heat resistance, an aromatic compound is preferred.
[0043] Examples of aromatic tetracarboxylic dianhydrides include pyromellitic dianhydride, 3,3',4,4'-benzophenone tetracarboxylic dianhydride, 3,3',4,4'-biphenylsulfone tetracarboxylic dianhydride, 1,4,5,8-naphthalene tetracarboxylic dianhydride, 2,3,6,7-naphthalene tetracarboxylic dianhydride, 3,3',4,4'-biphenyl ether tetracarboxylic dianhydride, 3,3',4,4'-dimethyldiphenylsilane tetracarboxylic dianhydride, 3,3',4,4'-tetraphenylsilane tetracarboxylic dianhydride, 1,2,3,4-furan tetracarboxylic dianhydride, 4,4'-bis(3,4-dicarboxyphenoxy)diphenyl sulfide dianhydride, 4,4 Examples of the dianhydride include 3,3',4,4'-bis(3,4-dicarboxyphenoxy)diphenylsulfone dianhydride, 4,4'-bis(3,4-dicarboxyphenoxy)diphenylpropane dianhydride, 3,3',4,4'-perfluoroisopropylidenediphthalic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,3,3',4'-biphenyltetracarboxylic dianhydride, bis(phthalic acid)phenylphosphine oxide dianhydride, p-phenylene-bis(triphenylphthalic acid) dianhydride, m-phenylene-bis(triphenylphthalic acid) dianhydride, bis(triphenylphthalic acid)-4,4'-diphenyl ether dianhydride, and bis(triphenylphthalic acid)-4,4'-diphenylmethane dianhydride.
[0044] Examples of the aliphatic tetracarboxylic dianhydride include butane tetracarboxylic dianhydride, 1,2,3,4-cyclobutane tetracarboxylic dianhydride, 1,3-dimethyl-1,2,3,4-cyclobutane tetracarboxylic dianhydride, 1,2,3,4-cyclopentane tetracarboxylic dianhydride, 2,3,5-tricarboxycyclopentyl acetic dianhydride, 3,5,6-tricarboxynorbonane-2-acetic dianhydride, 2,3,4,5-tetrahydrofuran tetracarboxylic dianhydride, 5-(2,5-dioxotetrahydrofuryl)-3-methyl-3-cyclohexene-1,2-dicarboxylic dianhydride, bicyclo[2,2,2]-oct-7-ene aliphatic or alicyclic tetracarboxylic acid dianhydrides such as 1,3,3a,4,5,9b-hexahydro-2,5-dioxo-3-furanyl)-naphtho[1,2-c]furan-1,3-dione, 1,3,3a,4,5,9b-hexahydro-5-methyl-5-(tetrahydro-2,5-dioxo-3-furanyl)-naphtho[1,2-c]furan-1,3-dione, and 1,3,3a,4,5,9b-hexahydro-8-methyl-5-(tetrahydro-2,5-dioxo-3-furanyl)-naphtho[1,2-c]furan-1,3-dione.
[0045] Among these, the tetracarboxylic acid dianhydride is preferably an aromatic tetracarboxylic acid dianhydride, specifically, for example, pyromellitic acid dianhydride, 3,3',4,4'-biphenyl tetracarboxylic acid dianhydride, 2,3,3',4'-biphenyl tetracarboxylic acid dianhydride, 3,3',4,4'-biphenyl ether tetracarboxylic acid dianhydride, 3,3',4,4'-benzophenone tetracarboxylic acid dianhydride, further, pyromellitic acid dianhydride, 3,3',4,4'-biphenyl tetracarboxylic acid dianhydride, 3,3',4,4'-benzophenone tetracarboxylic acid dianhydride is more preferable, and 3,3',4,4'-biphenyl tetracarboxylic acid dianhydride is particularly preferable.
[0046] The tetracarboxylic dianhydrides may be used alone or in combination of two or more. In addition, when two or more kinds of tetracarboxylic dianhydrides are used in combination, aromatic tetracarboxylic dianhydrides or aliphatic tetracarboxylic dianhydrides may be used in combination, or an aromatic tetracarboxylic dianhydride and an aliphatic tetracarboxylic dianhydride may be used in combination.
[0047] On the other hand, the diamine compound is a diamine compound having two amino groups in the molecular structure. The diamine compound may be either an aromatic or aliphatic compound, but is preferably an aromatic compound.
[0048] Examples of the diamine compound include p-phenylenediamine, m-phenylenediamine, 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylethane, 4,4'-diaminodiphenylether, 4,4'-diaminodiphenylsulfide, 4,4'-diaminodiphenylsulfone, 1,5-diaminonaphthalene, 3,3-dimethyl-4,4'-diaminobiphenyl, 5-amino-1-(4'-aminophenyl)-1,3,3-trimethylindane, 6-amino-1-(4'-aminophenyl)-1,3 ,3-Trimethylindane, 4,4'-diaminobenzanilide, 3,5-diamino-3'-trifluoromethylbenzanilide, 3,5-diamino-4'-trifluoromethylbenzanilide, 3,4'-diaminodiphenyl ether, 2,7-diaminofluorene, 2,2-bis(4-aminophenyl)hexafluoropropane, 4,4'-methylene-bis(2-chloroaniline), 2,2',5,5'-tetrachloro-4,4'-diaminobiphenyl, 2,2'-dichloro-4,4'-diamino-5,5'-diamine Toxobiphenyl, 3,3'-dimethoxy-4,4'-diaminobiphenyl, 4,4'-diamino-2,2'-bis(trifluoromethyl)biphenyl, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, 1,4-bis(4-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)-biphenyl, 1,3'-bis(4-aminophenoxy)benzene, 9,9-bis(4-aminophenyl)fluorene aromatic diamines such as 4,4'-(p-phenyleneisopropylidene)bisaniline, 4,4'-(m-phenyleneisopropylidene)bisaniline, 2,2'-bis[4-(4-amino-2-trifluoromethylphenoxy)phenyl]hexafluoropropane, and 4,4'-bis[4-(4-amino-2-trifluoromethyl)phenoxy]-octafluorobiphenyl; aromatic diamines having two amino groups bonded to an aromatic ring and a heteroatom other than the nitrogen atom of the amino group, such as diaminotetraphenylthiophene;1,1-meta-xylylenediamine, 1,3-propanediamine, tetramethylenediamine, pentamethylenediamine, octamethylenediamine, nonamethylenediamine, 4,4-diaminoheptamethylenediamine, 1,4-diaminocyclohexane, isophoronediamine, tetrahydrodicyclopentadienylenediamine, hexahydro-4,7-methanoindanidinediamine, tricyclo[6,2,1,0; 2.7 ]-undecylenedimethyldiamine, 4,4'-methylenebis(cyclohexylamine), and other aliphatic diamines and alicyclic diamines.
[0049] Among these, the diamine compound is preferably an aromatic diamine compound, specifically, for example, p-phenylenediamine, m-phenylenediamine, 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 4,4'-diaminodiphenyl sulfide, 4,4'-diaminodiphenyl sulfone, and particularly, 4,4'-diaminodiphenyl ether and p-phenylenediamine are preferable.
[0050] The diamine compounds may be used alone or in combination of two or more. When two or more diamine compounds are used in combination, aromatic diamine compounds or aliphatic diamine compounds may be used in combination, or an aromatic diamine compound and an aliphatic diamine compound may be used in combination.
[0051] Among these, from the viewpoint of heat resistance, aromatic polyimides (specifically, imidized products of polyamic acids (precursors of polyimide resins), which are polymers of aromatic tetracarboxylic dianhydrides and aromatic diamine compounds) are preferred as polyimides. The aromatic polyimide is more preferably a polyimide having a structural unit represented by the following general formula (PI1).
[0052] [ka]
[0053] In the general formula (PI1), R P1 represents a phenyl group or a biphenyl group, and R P2 represents a divalent aromatic group. R P2 Examples of the divalent aromatic group represented by the formula (I) include a phenylene group, a naphthyl group, a biphenyl group, a diphenyl ether group, etc. As the divalent aromatic group, a phenylene group and a biphenyl group are preferred from the viewpoint of flexural durability.
[0054] The number average molecular weight of the polyimide is preferably 5,000 or more and 100,000 or less, more preferably 7,000 or more and 50,000 or less, and further preferably 10,000 or more and 30,000 or less.
[0055] The number average molecular weight of polyimide is measured by gel permeation chromatography (GPC) under the following measurement conditions. Column: Tosoh TSKgel α-M (7.8 mm ID x 30 cm) Eluent: DMF (dimethylformamide) / 30mM LiBr / 60mM phosphoric acid ·Flow rate: 0.6mL / min ·Injection volume: 60μL Detector: RI (Differential Refractive Index Detector)
[0056] The resin content in the substrate layer is preferably 80% by mass or more, more preferably 85% by mass or more, and even more preferably 90% by mass or more, based on the total mass of the substrate layer.
[0057] [Additives] The fuser belt according to the present disclosure may contain known additives such as fillers, lubricants, etc. in addition to the resin, specific aggregates, and non-entangled fibrous carbon.
[0058] From the viewpoints of thermal conductivity and mechanical strength, the thickness of the base layer is preferably 30 μm or more and 200 μm or less, more preferably 50 μm or more and 150 μm or less, and particularly preferably 70 μm or more and 120 μm or less.
[0059] [Physical Properties] (Thermal Conductivity) The thermal conductivity of the base material layer is preferably 0.5 W / m·K or more and 10 W / m·K or less, more preferably 0.6 W / m·K or more and 10 W / m·K or less, and even more preferably 0.8 W / m·K or more and 10 W / m·K or less.
[0060] The thermal conductivity of the substrate layer is measured as follows. First, a cutter blade is inserted into the elastic layer / base layer interface from the surface layer side of the fixing belt, and the blade is advanced horizontally to the interface to scrape off the base layer, thereby peeling off the elastic layer and release layer from the base layer. The thermal conductivity of the obtained layer to be measured is measured under a load of 50 g by thermal wave analysis using ai-phase (manufactured by ai-phase Co., Ltd.).
[0061] (Tensile elongation) The tensile elongation of the base layer is preferably 5% or more and 40% or less, more preferably 7% or more and 40% or less, and even more preferably 10% or more and 40% or less.
[0062] The tensile elongation of the substrate layer is measured as follows. First, the base layer and the release layer are peeled off from the fixing belt in the same manner as in the measurement of thermal conductivity. First, a dumbbell-shaped test piece with a neck width of 5 mm is cut out from the obtained base layer. The test piece is subjected to a tensile test at a speed of 10 mm / min using a load tester (manufactured by Aikoh Engineering Co., Ltd.), and the tensile elongation is calculated from the elongation at which the test piece breaks.
[0063] [Formation of base layer] The substrate layer is obtained by preparing a substrate layer forming coating liquid containing a resin and additives used as necessary, applying the obtained substrate layer forming coating liquid onto a cylindrical substrate, and drying the substrate layer forming coating liquid. The substrate layer forming coating liquid contains a resin, a specific aggregate, and other components used as necessary (unentangled fibrous carbon, additives, etc.). When the resin is a polyimide, a coating liquid for forming a base layer containing a polyamic acid (a precursor of a polyimide resin) and additives used as necessary is prepared, and the obtained coating liquid for forming a base layer is applied onto a cylindrical base material and baked (i.e., imidization).
[0064] When preparing the coating liquid for forming the base layer, it is preferable to simultaneously produce the specific assembly. Specifically, a method includes preparing a precursor liquid containing a resin and fibrous carbon (also referred to as a precursor liquid preparation process), producing a specific aggregate in this precursor liquid system (also referred to as a specific aggregate production process), and obtaining a coating liquid for forming a base layer containing the resin and the specific aggregate. The precursor liquid preparation step and the specific assembly manufacturing step will be described below.
[0065] (Precursor liquid preparation process) In the precursor liquid preparation step, it is preferable to first mix the fibrous carbon with a dispersion medium to prepare a dispersion liquid in which the fibrous carbon is dispersed. Here, the dispersion medium may be an organic solvent in which the fibrous carbon does not dissolve or is difficult to dissolve, and the resin can be dissolved. For example, when polyamic acid (a precursor of polyimide resin) is used as the resin, the dispersion medium may be N-methyl-2-pyrrolidone (NMP), dimethyl sulfoxide (DMSO), 1,3-dimethyl-2-imidazolidinone (DMI), etc. Here, the content of the fibrous carbon in the dispersion liquid is preferably 0.1 mass % or more and 10 mass % or less (more preferably 0.3 mass % or more and 5 mass % or less) based on the total mass of the dispersion liquid.
[0066] The obtained dispersion liquid is preferably subjected to a high-pressure dispersion treatment. By performing the high-pressure dispersion treatment, the fibrous carbon in the dispersion liquid is loosened and individually isolated, and further, the length of the fibrous carbon in the dispersion liquid is adjusted. Here, the conditions of the high pressure dispersion treatment may be any conditions that allow the fibrous carbon to be individually isolated and the length of the fibrous carbon to be adjusted to a desired value. For example, the high pressure dispersion treatment is preferably performed under a liquid temperature of the dispersion liquid of 30°C or more and 60°C or less, and a pressure of 20MPa or more and 100MPa or less (preferably, 40MPa or more and 80MPa or less). The high-pressure dispersion treatment uses a high-pressure homogenizer.
[0067] The length of the fibrous carbon in the dispersion liquid is preferably adjusted to about 1 μm or more and 100 μm or less (preferably, 3 μm or more and 50 μm or less). Here, the length of the fibrous carbon in the dispersion liquid can be measured by observation with an optical microscope or an electron microscope. The maximum diameter of a specific aggregate can be controlled by the length of the fibrous carbon in the dispersion liquid. Specifically, there is a tendency that the longer the fibrous carbon, the larger the maximum diameter of the aggregate that can be produced.
[0068] In the precursor liquid preparation step, a resin is subsequently added to the dispersion liquid obtained as described above to prepare a precursor liquid. The amount of resin added is preferably about 1% by mass or more and 20% by mass or less (more preferably 3% by mass or more and 15% by mass or less) relative to the total mass of the dispersion.
[0069] (Specific aggregate manufacturing process) In the specific assembly production step, the precursor liquid obtained in the precursor liquid preparation step is stirred by a planetary mixer, and the specific assembly is produced in the system. By stirring the precursor liquid with a planetary mixer, the fibrous carbon that was individually isolated in the precursor liquid gradually becomes entangled and lumps, producing a specific aggregate.
[0070] Here, the stirring conditions using the planetary mixer may be any conditions under which specific aggregates having the desired maximum diameter can be obtained. For example, the stirring conditions are preferably such that the temperature of the precursor liquid is 25° C. or higher and 40° C. or lower, and the stirring is carried out for 10 minutes or longer and 60 minutes or shorter. The maximum diameter of a particular aggregate can be controlled by the stirring conditions. Specifically, the longer the stirring time using a planetary mixer, the larger the maximum diameter of the aggregates that can be produced tends to be.
[0071] In the specific aggregate manufacturing process, all of the fibrous carbon contained in the precursor liquid may become specific aggregates, or some fibrous carbon that does not form specific aggregates (i.e., fibrous carbon that is not entangled with each other) may remain together with the specific aggregates.
[0072] In this manner, a mixed liquid containing the resin and the specific aggregate is obtained. To the obtained mixture, other components (unentangled fibrous carbon, additives, etc.) are added as necessary to obtain a coating liquid for forming a base layer. The obtained mixture may be diluted with an organic solvent to adjust the viscosity of the coating liquid.
[0073] [Elastic layer] The base layer of the fixing belt according to the present disclosure includes an elastic material and an aggregate (that is, a specific aggregate) formed by a plurality of fibrous carbons entangled with one another. The maximum diameter of the specific aggregate in the elastic layer is 15% or less of the thickness of the elastic layer.
[0074] [Specific aggregate] The specific mass in the elastic layer is used as a heat conducting material. As described above, the maximum diameter of the specific aggregate in the elastic layer is preferably 15% or less, more preferably 10% or less, of the elastic layer thickness, while the maximum diameter of the specific aggregate is more preferably 2% or more of the elastic layer thickness.
[0075] From the viewpoint of smooth heat transfer at the interface between the base layer and the elastic layer, the maximum diameter of the specific aggregates in the elastic layer is preferably 60 μm or less, and more preferably 30 μm or less. The lower limit of the maximum diameter of the specific aggregates in the elastic layer is, for example, 5 μm or more.
[0076] Unless otherwise specified, the specific aggregate used in the elastic layer has the same definition as the specific aggregate used in the base layer, and the preferred embodiments are also the same.
[0077] From the viewpoint of smoother heat transfer at the interface between the base layer and the elastic layer, the content A2 of the specific aggregate in the elastic layer is preferably 0.1 mass % or more and 40 mass % or less, more preferably 1 mass % or more and 35 mass % or less, even more preferably 5 mass % or more and 30 mass % or less, and particularly preferably 15 mass % or more and 25 mass % or less, relative to the total mass of the elastic layer.
[0078] In the fixing belt according to the present disclosure, it is preferable that the content A1 of the specific aggregate contained in the base layer and the total mass A2 of the specific aggregate contained in the elastic layer satisfy the relationship A1≦A2 on a mass basis. In addition, in the fixing belt according to the present disclosure, it is preferable that the above-mentioned relationship A1≦A2 is satisfied, and the content A1 of the specific aggregate is 0.1 mass % or more and 20 mass % or less with respect to the total mass of the base material layer, and the content A2 of the specific aggregate is 0.1 mass % or more and 40 mass % or less with respect to the total mass of the elastic layer.
[0079] On the other hand, from the viewpoint of belt temperature stability during long-term continuous paper feed, the content A1 of the specific aggregate contained in the base layer and the total mass A2 of the specific aggregate contained in the elastic layer may satisfy the relationship A1>A2 on a mass basis.
[0080] [Disjointed fibrous carbon] From the viewpoint of further increasing thermal conductivity, the elastic layer preferably contains non-entangled fibrous carbon in addition to the specific aggregates described above. That is, the elastic layer preferably contains an elastic material, specific aggregates, and non-entangled fibrous carbon.
[0081] Here, the non-entangled fibrous carbon used in the elastic layer is synonymous with the non-entangled fibrous carbon used in the base layer, and the preferred embodiments are also the same.
[0082] When the elastic layer contains non-entangled fibrous carbon, the content thereof is preferably more than 0 mass% and not more than 20 mass%, more preferably more than 0.1 mass% and not more than 15 mass%, more preferably 0.3 mass% or more and 10 mass% or less, and particularly preferably 0.5 mass% or more and 8 mass% or less, relative to the total mass of the elastic layer.
[0083] In addition, in the elastic layer, it is preferable that the content A of the specific aggregate and the content B of the non-entangled fibrous carbon satisfy the relationship A≧B on a mass basis. In addition, the elastic layer preferably has a ratio (A / (A+B)) of the content A of specific aggregates to the total amount of the content A of specific aggregates and the content B of unentangled fibrous carbon, on a mass basis, of 0.50 or more and 0.95 or less, and more preferably 0.75 or more and 0.95 or less.
[0084] [Elastic material] Examples of the elastic material contained in the elastic layer include fluororesin, silicone resin, silicone rubber, fluororubber, fluorosilicone rubber, etc. Among them, as the elastic material, silicone rubber and fluororubber are preferable, and silicone rubber is more preferable, from the viewpoints of heat resistance, thermal conductivity, insulation, etc.
[0085] Examples of silicone rubber include RTV silicone rubber, HTV silicone rubber, and liquid silicone rubber. Specific examples of silicone rubber include polydimethyl silicone rubber (MQ), methyl vinyl silicone rubber (VMQ), methyl phenyl silicone rubber (PMQ), and fluoro silicone rubber (FVMQ).
[0086] Silicone rubbers that are primarily crosslinked by addition reaction are preferred. Silicone rubbers are known to have various types of functional groups, and preferred examples include dimethyl silicone rubbers having methyl groups, methylphenyl silicone rubbers having methyl and phenyl groups, and vinyl silicone rubbers having vinyl groups (vinyl group-containing silicone rubbers). As the silicone rubber, a vinyl silicone rubber having a vinyl group is more preferable, and a silicone rubber having an organopolysiloxane structure having a vinyl group and a hydrogen organopolysiloxane structure having a hydrogen atom (SiH) bonded to a silicon atom is even more preferable.
[0087] Examples of the fluororubber include vinylidene fluoride rubber, tetrafluoroethylene / propylene rubber, tetrafluoroethylene / perfluoromethylvinyl ether rubber, phosphazene rubber, and fluoropolyether.
[0088] The elastic material preferably contains silicone rubber as a main component (that is, the elastic material contains silicone rubber in an amount of 50% by mass or more relative to the total mass of the elastic material). The content of the silicone rubber is more preferably 90% by mass or more, further preferably 99% by mass or more, and may be 100% by mass, based on the total mass of the elastic material used in the elastic layer.
[0089] The content of the elastic material in the elastic layer is preferably 60% by mass or more, more preferably 70% by mass or more, and even more preferably 80% by mass or more, based on the total mass of the base layer.
[0090] [Additives] In addition to the above-mentioned components, the elastic layer may contain additives such as a specific aggregate, an inorganic filler other than fibrous carbon, a softener (e.g., paraffin-based), a processing aid (e.g., stearic acid), an antioxidant (e.g., amine-based), and a vulcanizing agent (e.g., sulfur, metal oxide, peroxide).
[0091] The thickness (film thickness) of the elastic layer is, for example, preferably 30 μm or more and 600 μm or less, and more preferably 100 μm or more and 500 μm or less.
[0092] [Physical Properties] (Thermal Conductivity) The thermal conductivity of the elastic layer is preferably 1.0 W / m·K or more and 4.5 W / m·K or less, more preferably 2.0 W / m·K or more and 4.5 W / m·K or less, and even more preferably 3.5 W / m·K or more and 4.5 W / m·K or less.
[0093] The thermal conductivity of the elastic layer is measured as follows. First, a cutter blade is used to make an incision from the release layer side of the fixing belt to the release layer / elastic layer interface, and then the release layer is peeled off by gripping only the release layer with a hand and pulling it in the radial direction of 0° while rotating the belt. After that, a cutter blade is inserted into the elastic layer / base layer interface, and the blade is advanced horizontally to the interface to peel off the base layer. The thermal conductivity of the obtained elastic layer is measured under a load of 50 g by thermal wave analysis using ai-phase (manufactured by ai-phase Co., Ltd.).
[0094] (Young's Modulus) The Young's modulus of the elastic layer is preferably 0.2 MPa or more and 1.0 MPa or less, more preferably 0.2 MPa or more and 0.8 MPa or less, and even more preferably 0.2 MPa or more and 0.6 MPa or less.
[0095] The Young's modulus of the elastic layer is measured as follows. First, the base layer and the release layer are peeled off from the fixing belt in the same manner as in the measurement of thermal conductivity. The obtained elastic layer of the subject is measured with Rheovibron (manufactured by Orientec Co., Ltd.) at an amplitude of 50 μm and a frequency of 10 Hz, and the value at 150° C. is used.
[0096] [Formation of elastic layer] The elastic layer may be formed by a known method, for example, a coating method. When silicone rubber is used as the elastic material of the elastic layer, for example, first prepare a coating liquid for forming an elastic layer, which contains a liquid silicone rubber that is cured by heating to become silicone rubber. Next, the coating liquid for forming an elastic layer is applied onto the base layer to form a coating film, and the coating film is vulcanized as necessary to form an elastic layer on the base layer. In addition, in the vulcanization of the coating film, the vulcanization temperature can be, for example, 150°C or more and 250°C or less, and the vulcanization time can be, for example, 30 minutes or more and 120 minutes or less.
[0097] When preparing the coating liquid for forming the elastic layer, it is preferable to simultaneously produce a specific assembly. Specifically, one example of such a method includes preparing a precursor liquid containing an elastic material and fibrous carbon (also referred to as a precursor liquid preparation process), producing a specific aggregate in the precursor liquid system (also referred to as a specific aggregate production process), and obtaining a coating liquid containing the elastic material and the specific aggregate. Here, the precursor liquid preparation step and the specific assembly manufacturing step will be described.
[0098] (Precursor liquid preparation process) In the precursor liquid preparation step, it is preferable to first mix the fibrous carbon with a dispersion medium to prepare a dispersion liquid in which the fibrous carbon is dispersed. Here, the dispersion medium may be an organic solvent in which the fibrous carbon does not dissolve or is difficult to dissolve, but which the elastic material can dissolve in. For example, when silicone rubber is used as the elastic material, the dispersion medium may be butyl acetate, toluene, heptane, benzene, acetone, or the like. Here, the content of the fibrous carbon in the dispersion liquid is preferably 10 mass % or more and 40 mass % or less (more preferably 15 mass % or more and 30 mass % or less) based on the total mass of the dispersion liquid.
[0099] The obtained dispersion liquid is preferably subjected to a high-pressure dispersion treatment. By performing the high-pressure dispersion treatment, the fibrous carbon in the dispersion liquid is loosened and individually isolated, and further, the length of the fibrous carbon in the dispersion liquid is adjusted. Here, the conditions of the high pressure dispersion treatment may be any conditions that allow the fibrous carbon to be individually isolated and the length of the fibrous carbon to be adjusted to a desired value. For example, the high pressure dispersion treatment is preferably performed under a liquid temperature of the dispersion liquid of 30°C or more and 60°C or less, and a pressure of 20MPa or more and 100MPa or less (preferably, 40MPa or more and 80MPa or less). For the high pressure dispersion treatment, for example, a high pressure homogenizer is used.
[0100] The length of the fibrous carbon in the dispersion liquid is preferably adjusted to about 1.5 μm or more and 18 μm or less (preferably, 2 μm or more and 15 μm or less). Here, the length of the fibrous carbon in the dispersion liquid can be measured by observation with an optical microscope or an electron microscope. The maximum diameter of a specific aggregate can be controlled by the length of the fibrous carbon in the dispersion liquid. Specifically, there is a tendency that the longer the fibrous carbon, the larger the maximum diameter of the aggregate that can be produced.
[0101] In the precursor liquid preparation step, an elastic material is subsequently added to the dispersion liquid obtained as described above to prepare a precursor liquid. The amount of the elastic material added is preferably about 10% by mass or more and 90% by mass or less (more preferably, 15% by mass or more and 60% by mass or less) with respect to the total mass of the precursor liquid.
[0102] (Specific aggregate manufacturing process) In the specific assembly production step, the precursor liquid obtained in the precursor liquid preparation step is stirred by a planetary mixer, and the specific assembly is produced in the system. By stirring the precursor liquid with a planetary mixer, the fibrous carbon that was individually isolated in the precursor liquid gradually becomes entangled and lumps, producing a specific aggregate.
[0103] Here, the stirring conditions using the planetary mixer may be any conditions under which specific aggregates having the desired maximum diameter can be obtained. For example, the stirring conditions are preferably such that the temperature of the precursor liquid is 25° C. or more and 40° C. or less, and the stirring is carried out for 10 minutes or more and 60 minutes or less while drawing a vacuum. The maximum diameter of a particular aggregate can be controlled by the stirring conditions. Specifically, the longer the stirring time using a planetary mixer, the larger the maximum diameter of the aggregates that can be produced tends to be.
[0104] In the specific aggregate manufacturing process, all of the fibrous carbon contained in the precursor liquid may become specific aggregates, or some fibrous carbon that does not form specific aggregates (i.e., fibrous carbon that is not entangled with each other) may remain together with the specific aggregates.
[0105] In this manner, a mixed liquid containing the elastic material and the specific aggregate is obtained. To the obtained mixture, other components (unentangled fibrous carbon, additives, etc.) are added as necessary to obtain a coating liquid for forming an elastic layer. The obtained mixture may be diluted with an organic solvent to adjust the viscosity of the coating liquid.
[0106] [Release layer] The fixing belt according to the present disclosure has a release layer on the elastic layer. The release layer is a layer that plays a role in preventing the molten toner image from sticking to the surface (outer peripheral surface) that comes into contact with a recording medium during fixing.
[0107] The release layer is required to have, for example, heat resistance and releasability. From this viewpoint, it is preferable to use a heat-resistant release material as the material constituting the release layer, and specific examples thereof include fluororubber, fluororesin, silicone resin, polyimide resin, and the like. Among these, fluororesin is preferable as the heat-resistant release material. Specific examples of fluororesins include tetrafluoroethylene-perfluoroalkylvinyl ether copolymer (PFA), polytetrafluoroethylene (PTFE), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), polyethylene-tetrafluoroethylene copolymer (ETFE), polyvinylidene fluoride (PVDF), polychlorotrifluoroethylene (PCTFE), and vinyl fluoride (PVF).
[0108] The surface of the release layer on the elastic layer side may be subjected to a surface treatment. The surface treatment may be a wet treatment or a dry treatment, and examples of the surface treatment include a liquid ammonia treatment, an excimer laser treatment, and a plasma treatment.
[0109] The thickness of the release layer is preferably 10 μm or more and 100 μm or less, and more preferably 20 μm or more and 50 μm or less.
[0110] The release layer may be formed by a known method, for example, a coating method. Alternatively, a tubular release layer may be prepared in advance and coated on the outer periphery of the elastic layer to form the release layer. Note that an adhesive layer (e.g., an adhesive layer containing a silane coupling agent having an epoxy group) may be formed on the inner surface of the tubular release layer, and then the outer periphery may be coated.
[0111] The thickness of the fixing belt according to the present disclosure is, for example, preferably 0.06 mm or more and 0.90 mm or less, more preferably 0.15 mm or more and 0.70 mm or less, and even more preferably 0.10 mm or more and 0.60 mm or less.
[0112] [Use of fixing belt member] The fixing belt according to the present disclosure may be applied, for example, to either a heating belt or a pressure belt, but as described above, it is preferably applied to a fixing method in which a heat source is present inside the fixing belt and heat from the heat source is transferred to a toner image via the fixing belt.
[0113] <Fixing device> The fixing device according to the present disclosure has various configurations, for example, a fixing device that includes a first rotating body and a second rotating body arranged in contact with the outer surface of the first rotating body, and fixes a toner image by inserting a recording medium having a toner image formed on the surface into a contact portion between the first rotating body and the second rotating body. The fixing belt according to the present disclosure is applied as at least one of the first rotating body and the second rotating body. In addition, in the fixing device according to the present disclosure, it is preferable that a heat source is present inside at least one of the first rotating body and the second rotating body to which the fixing belt according to the present disclosure is applied.
[0114] As an embodiment of a fixing device according to the present disclosure, a fixing device including a heating belt to which the fixing belt according to the present disclosure is applied and a heating roll will be described below. The fixing device according to the present disclosure is not limited to the above embodiment, and may be a fixing device including a heating belt and a pressure belt, or a fixing device including a heating roll and a pressure belt. In these fixing devices, the fixing belt according to the present disclosure may be applied to either the heating belt or the pressure belt.
[0115] (Embodiment of Fixing Device) A first embodiment of the fixing device will be described with reference to Fig. 2. Fig. 2 is a schematic diagram showing an example of an embodiment of the fixing device (that is, fixing device 80).
[0116] 2, the fixing device 80 includes, for example, a fixing belt module 86 equipped with a heating belt 84 (an example of a first rotating body), and a pressure roll 88 (an example of a second rotating body) arranged to press against the heating belt 84 (fixing belt module 86). For example, a pinch region N (nip portion) is formed at the contact portion between the heating belt 84 (fixing belt module 86) and the pressure roll 88. In the pinch region N, a sheet K (an example of a recording medium) is pressurized and heated, and a toner image is fixed.
[0117] The fixing belt module 86 includes, for example, an endless heating belt 84, a heating pressure roll 89 around which the heating belt 84 is wound on the pressure roll 88 side and which is rotated by the rotational force of a motor (not shown) and presses the heating belt 84 from its inner surface against the pressure roll 88 side, and a support roll 90 which supports the heating belt 84 from the inside at a position different from the heating pressure roll 89. The fixing belt module 86 includes, for example, a support roll 92 arranged on the outside of the heating belt 84 to define its rotational path, a posture correction roll 94 to correct the posture of the heating belt 84 from the heating pressure roll 89 to the support roll 90, and a support roll 98 to apply tension to the heating belt 84 from its inner surface downstream of the clamping area N formed by the heating belt 84 and the pressure roll 88.
[0118] The fixing belt module 86 is provided, for example, between the heating belt 84 and the heating pressure roll 89 so that a sheet-like sliding member 82 is interposed. The sliding member 82 is provided, for example, so that its sliding surface comes into contact with the inner circumferential surface of the heating belt 84 , and is involved in the retention and supply of oil present between the sliding member 82 and the heating belt 84 . Here, the sliding member 82 is provided in a state in which both ends thereof are supported by supporting members 96, for example.
[0119] Inside the heating and pressing roll 89, for example, a halogen heater 89A (an example of a heat source) is provided.
[0120] The support roll 90 is, for example, a cylindrical roll made of aluminum, and has a halogen heater 90A (an example of a heat source) disposed therein so as to heat the heating belt 84 from the inner circumferential surface side. At both ends of the support roll 90, for example, spring members (not shown) are provided to press the heating belt 84 outward.
[0121] The support roll 92 is a cylindrical roll made of, for example, aluminum, and a release layer made of fluororesin having a thickness of 20 μm is formed on the surface of the support roll 92. The release layer of the support roll 92 is formed, for example, to prevent toner and paper powder from the outer circumferential surface of the heating belt 84 from accumulating on the support roll 92 . Inside the support roll 92, for example, a halogen heater 92A (an example of a heat source) is disposed, and the heating belt 84 is heated from the outer circumferential surface side.
[0122] That is, for example, the heating belt 84 is heated by a heating pressure roll 89 and a supporting roll 90 and a supporting roll 92 .
[0123] The posture correction roll 94 is, for example, a cylindrical roll made of aluminum, and an end position measuring mechanism (not shown) that measures the end position of the heating belt 84 is disposed near the posture correction roll 94. The posture correction roll 94 is provided with, for example, an axial displacement mechanism (not shown) that displaces the contact position in the axial direction of the heating belt 84 in accordance with the measurement results of the end position measuring mechanism, and is configured to control the meandering of the heating belt 84.
[0124] On the other hand, the pressure roll 88 is, for example, supported rotatably and is provided so as to be pressed against the portion where the heating belt 84 is wound around the heating pressure roll 89 by a biasing means such as a spring (not shown). As a result, as the heating belt 84 (heating pressure roll 89) of the fixing belt module 86 rotates in the direction of arrow S, the pressure roll 88 rotates in the direction of arrow R, following the heating belt 84 (heating pressure roll 89).
[0125] Then, the paper K having an unfixed toner image (not shown) is transported in the direction of arrow P and guided to a pinch area N of the fixing device 80. Then, when the paper K passes through the pinch area N, the unfixed toner image on the paper K is fixed by pressure and heat acting on the pinch area N.
[0126] In the fixing device 80, a form in which a halogen heater (halogen lamp) is applied as an example of multiple heat sources has been described, but this is not limited to this, and a radiant lamp heating element (a heating element that emits radiation (infrared rays, etc.)) other than a halogen heater, or a resistive heating element (a heating element that generates Joule heat by passing an electric current through a resistor: for example, a film having resistance formed on a ceramic substrate and then fired) may also be applied.
[0127] <Image forming device> Next, the image forming apparatus according to the present disclosure will be described. The image forming apparatus according to the present disclosure includes an image carrier, a charging means for charging the surface of the image carrier, an electrostatic latent image forming means for forming an electrostatic latent image on the surface of the charged image carrier, a developing means for developing the electrostatic latent image formed on the surface of the image carrier with a developer containing toner to form a toner image, a transfer means for transferring the toner image to the surface of a recording medium, and a fixing means for fixing the toner image to the recording medium. As the fixing means, the fixing device according to the present disclosure is applied.
[0128] Here, in the image forming apparatus according to the present disclosure, the fixing device may be formed as a cartridge so as to be detachably attached to the image forming apparatus, i.e., the image forming apparatus according to the present disclosure may include the fixing device according to the present disclosure as a component device of a process cartridge.
[0129] Hereinafter, an image forming apparatus according to the present disclosure will be described with reference to the drawings. FIG. 3 is a schematic diagram showing an example of an embodiment of an image forming apparatus according to the present disclosure.
[0130] 3, the image forming apparatus 100 according to the present disclosure is, for example, an intermediate transfer type image forming apparatus generally called a tandem type, and includes a plurality of image forming units 1Y, 1M, 1C, and 1K in which toner images of each color component are formed by an electrophotographic method, a primary transfer section 10 that sequentially transfers (primary transfer) the toner images of each color component formed by each image forming unit 1Y, 1M, 1C, and 1K onto an intermediate transfer belt 15, a secondary transfer section 20 that collectively transfers (secondary transfer) the superimposed toner images transferred onto the intermediate transfer belt 15 onto a recording medium, paper K, and a fixing device 80 that fixes the secondarily transferred image onto the paper K. The image forming apparatus 100 also has a control section 40 that controls the operation of each device (each section).
[0131] The fixing device 80 is an embodiment of the fixing device according to the present disclosure described above. Note that the image forming apparatus 100 is not limited to the fixing device 80 as long as it includes the fixing device according to the present disclosure.
[0132] Each of the image forming units 1Y, 1M, 1C, and 1K of the image forming apparatus 100 includes a photoconductor 11 that rotates in the direction of arrow A as an example of an image carrier that carries a toner image formed on its surface.
[0133] Around the photoconductor 11, there is provided a charger 12 as an example of a charging means for charging the photoconductor 11, and there is provided a laser exposure device 13 (the exposure beam is indicated by the symbol Bm in the figure) as an example of a latent image forming means for writing an electrostatic latent image on the photoconductor 11.
[0134] In addition, around the photoconductor 11, there is provided a developing device 14 as an example of a developing means, which contains each color component toner and makes the electrostatic latent image on the photoconductor 11 visible using the toner, and there is provided a primary transfer roll 16 which transfers each color component toner image formed on the photoconductor 11 to an intermediate transfer belt 15 at the primary transfer section 10.
[0135] Furthermore, a photoreceptor cleaner 17 that removes residual toner on the photoreceptor 11 is provided around the photoreceptor 11, and electrophotographic devices including a charger 12, a laser exposure device 13, a developer 14, a primary transfer roll 16, and the photoreceptor cleaner 17 are sequentially arranged along the rotation direction of the photoreceptor 11. These image forming units 1Y, 1M, 1C, and 1K are arranged in a substantially linear fashion in the order of yellow (Y), magenta (M), cyan (C), and black (K) from the upstream side of the intermediate transfer belt 15.
[0136] The intermediate transfer belt 15, which is an intermediate transfer body, is a film-like pressure belt that has a base layer of resin such as polyimide or polyamide and contains an appropriate amount of antistatic agent such as carbon black. 6 Ωcm or more 10 14 It is formed to have a resistivity of Ωcm or less, and its thickness is, for example, about 0.1 mm.
[0137] The intermediate transfer belt 15 is driven (rotated) in a circular manner by various rolls at a speed suited to the purpose in the direction B shown in Fig. 3. The various rolls include a drive roll 31 driven by a motor (not shown) excellent in constant speed performance to rotate the intermediate transfer belt 15, a support roll 32 supporting the intermediate transfer belt 15 extending in a substantially straight line along the arrangement direction of the photoconductors 11, a tensioning roll 33 that applies tension to the intermediate transfer belt 15 and functions as a correction roll to prevent the intermediate transfer belt 15 from meandering, a back roll 25 provided in the secondary transfer unit 20, and a cleaning back roll 34 provided in a cleaning unit that scrapes off residual toner on the intermediate transfer belt 15.
[0138] The primary transfer section 10 is composed of a primary transfer roll 16 arranged opposite the photoconductor 11 with an intermediate transfer belt 15 sandwiched therebetween. The primary transfer roll 16 is composed of a core body and a sponge layer as an elastic layer fixed to the periphery of the core body. The core body is a cylindrical rod made of a metal such as iron or SUS. The sponge layer is formed of a blend rubber of NBR, SBR and EPDM mixed with a conductive agent such as carbon black, and has a volume resistivity of 10 7.5Ωcm or more 10 8.5 It is a sponge-like cylindrical roll with a surface resistance of less than Ωcm.
[0139] The primary transfer roll 16 is arranged in pressure contact with the photoconductor 11 with the intermediate transfer belt 15 sandwiched therebetween, and furthermore, a voltage (primary transfer bias) of the opposite polarity to the charge polarity of the toner (negative polarity; the same applies below) is applied to the primary transfer roll 16. As a result, the toner images on the photoconductors 11 are electrostatically attracted to the intermediate transfer belt 15 in sequence, and superimposed toner images are formed on the intermediate transfer belt 15.
[0140] The secondary transfer unit 20 includes a back roll 25 and a secondary transfer roll 22 that is disposed on the toner image bearing surface side of the intermediate transfer belt 15 .
[0141] The back roll 25 is made of a tube of EPDM and NBR blend rubber with carbon dispersed on the surface, and the inside is made of EPDM rubber. 7 Ω / □ or more 10 10 The hardness is set to, for example, 70° (Asker C: manufactured by Kobunshi Keiki Co., Ltd., the same applies below.) The back roll 25 is disposed on the back side of the intermediate transfer belt 15 to constitute an opposing electrode of the secondary transfer roll 22, and is in contact with a metallic power supply roll 26 to which a secondary transfer bias is stably applied.
[0142] On the other hand, the secondary transfer roll 22 is composed of a core body and a sponge layer as an elastic layer fixed around the core body. The core body is a cylindrical rod made of a metal such as iron or SUS. The sponge layer is made of a blend rubber of NBR, SBR and EPDM mixed with a conductive agent such as carbon black, and has a volume resistivity of 10 7.5 Ωcm or more 10 8.5 It is a sponge-like cylindrical roll with a surface resistance of less than Ωcm.
[0143] The secondary transfer roll 22 is placed in pressure contact with the back roll 25 with the intermediate transfer belt 15 sandwiched therebetween, and further, the secondary transfer roll 22 is grounded to form a secondary transfer bias between the secondary transfer roll 22 and the back roll 25, thereby secondarily transferring the toner image onto the paper K transported to the secondary transfer section 20.
[0144] In addition, downstream of the secondary transfer section 20 of the intermediate transfer belt 15, an intermediate transfer belt cleaner 35 that removes residual toner and paper dust on the intermediate transfer belt 15 after the secondary transfer and cleans the surface of the intermediate transfer belt 15 is provided so as to be freely movable toward and away from the intermediate transfer belt 15.
[0145] The intermediate transfer belt 15, the primary transfer section 10 (the primary transfer roll 16), and the secondary transfer section 20 (the secondary transfer roll 22) correspond to an example of a transfer unit.
[0146] Meanwhile, upstream of the yellow image forming unit 1Y, there is provided a reference sensor (home position sensor) 42 that generates a reference signal that serves as a reference for timing image formation in each of the image forming units 1Y, 1M, 1C, and 1K. This reference sensor 42 generates a reference signal by recognizing a mark provided on the back side of the intermediate transfer belt 15, and each of the image forming units 1Y, 1M, 1C, and 1K is configured to start image formation in response to an instruction from the control unit 40 based on the recognition of this reference signal. Further, an image density sensor 43 for adjusting image quality is disposed downstream of the black image forming unit 1K.
[0147] Furthermore, in the image forming apparatus according to the present disclosure, as a transport means for transporting the paper K, there are provided a paper storage section 50 for storing the paper K, a paper feed roll 51 for taking out and transporting the paper K accumulated in the paper storage section 50 at a predetermined timing, a transport roll 52 for transporting the paper K unwound by the paper feed roll 51, a transport guide 53 for sending the paper K transported by the transport roll 52 to the secondary transfer section 20, a transport belt 55 for transporting the paper K transported after secondary transfer by the secondary transfer roll 22 to the fixing device 60, and a fixing entrance guide 56 for guiding the paper K to the fixing device 60.
[0148] Next, a basic image forming process of the image forming apparatus according to the present disclosure will be described. In the image forming apparatus of the present disclosure, image data output from an image reading device (not shown) or a personal computer (PC) (not shown), etc., is subjected to image processing by an image processing device (not shown), and then image formation is performed by image forming units 1Y, 1M, 1C, and 1K.
[0149] The image processing device performs image processing on the input reflectance data, such as shading correction, positional deviation correction, brightness / color space conversion, gamma correction, and various image editing such as frame erasure, color editing, and movement editing. The image data that has undergone image processing is converted into color material gradation data of four colors, Y, M, C, and K, and is output to the laser exposure device 13.
[0150] In the laser exposure device 13, an exposure beam Bm emitted from, for example, a semiconductor laser is irradiated onto the photoconductor 11 of each of the image forming units 1Y, 1M, 1C, and 1K in accordance with the input color material gradation data. In each of the photoconductors 11 of the image forming units 1Y, 1M, 1C, and 1K, the surface is charged by the charger 12, and then the surface is scanned and exposed by the laser exposure device 13 to form an electrostatic latent image. The formed electrostatic latent image is developed into a toner image of each color of Y, M, C, and K by each of the image forming units 1Y, 1M, 1C, and 1K.
[0151] The toner images formed on the photoconductors 11 of the image forming units 1Y, 1M, 1C, and 1K are transferred onto the intermediate transfer belt 15 in the primary transfer section 10 where each photoconductor 11 comes into contact with the intermediate transfer belt 15. More specifically, in the primary transfer section 10, a voltage (primary transfer bias) of the opposite polarity to the charging polarity (negative polarity) of the toner is applied to the base material of the intermediate transfer belt 15 by the primary transfer roll 16, and the toner images are sequentially superimposed on the surface of the intermediate transfer belt 15 to perform the primary transfer.
[0152] After the toner images are sequentially primarily transferred onto the surface of the intermediate transfer belt 15, the intermediate transfer belt 15 moves to transport the toner images to the secondary transfer unit 20. When the toner images are transported to the secondary transfer unit 20, the transport means rotates the paper feed roll 51 in accordance with the timing at which the toner images are transported to the secondary transfer unit 20, and paper K of the desired size is supplied from the paper storage unit 50. The paper K supplied by the paper feed roll 51 is transported by the transport roll 52 and reaches the secondary transfer unit 20 via the transport guide 53. Before reaching the secondary transfer unit 20, the paper K is temporarily stopped, and an alignment roll (not shown) rotates in accordance with the movement timing of the intermediate transfer belt 15 on which the toner images are held, thereby aligning the position of the paper K with the position of the toner image.
[0153] In the secondary transfer section 20, the secondary transfer roll 22 is pressed against the back roll 25 via the intermediate transfer belt 15. At this time, the paper K, which has been transported in time, is sandwiched between the intermediate transfer belt 15 and the secondary transfer roll 22. At this time, when a voltage (secondary transfer bias) of the same polarity as the charging polarity (negative polarity) of the toner is applied from the power supply roll 26, a transfer electric field is formed between the secondary transfer roll 22 and the back roll 25. Then, the unfixed toner images held on the intermediate transfer belt 15 are electrostatically transferred collectively onto the paper K in the secondary transfer section 20, which is pressed by the secondary transfer roll 22 and the back roll 25.
[0154] Thereafter, the paper K onto which the toner image has been electrostatically transferred is transported as it is after being peeled off from the intermediate transfer belt 15 by the secondary transfer roll 22, and is transported to a transport belt 55 provided downstream of the secondary transfer roll 22 in the paper transport direction. The transport belt 55 transports the paper K to the fixing device 60 at an optimal transport speed for the fixing device 60. The unfixed toner image on the paper K transported to the fixing device 60 is fixed onto the paper K by being subjected to a fixing process using heat and pressure by the fixing device 60. The paper K on which the fixed image has been formed is then transported to an ejected paper storage section (not shown) provided in the ejection section of the image forming apparatus.
[0155] On the other hand, after the transfer to the paper K is completed, the residual toner remaining on the intermediate transfer belt 15 is transported to the cleaning section as the intermediate transfer belt 15 rotates, and is removed from the intermediate transfer belt 15 by the cleaning back roll 34 and the intermediate transfer belt cleaner 35.
[0156] Although the present embodiment has been described above, the present invention is not limited to the above embodiment, and various modifications, changes, and improvements are possible. EXAMPLES
[0157] The present invention will be described in more detail below with reference to examples, although the present invention is not limited to the following examples.
[0158] <Example 1> (Formation of base layer) A dispersion (hereinafter also referred to as "CNT 5% dispersion") was prepared by mixing N-methyl-2-pyrrolidone (NMP) and carbon nanotubes (manufactured by Showa Denko K.K.) in a mass ratio of 95:5. The obtained dispersion was subjected to a high-pressure dispersion treatment (conditions: liquid temperature 45°C, 50 MPa, number of valve passes (number of passes): 5) using a high-pressure homogenizer (HC3 manufactured by Sanmaru Machinery Co., Ltd.). Next, 528 parts by mass of a polyamic acid solution (TX-HMM (polyimide varnish) manufactured by Unitika Ltd., solid content concentration: 18% by mass, solvent: NMP) was added to 100 parts by mass of the dispersion liquid after the high pressure dispersion treatment to prepare a precursor liquid. The obtained precursor liquid was stirred for 15 minutes in a planetary mixer (Aikosha Seisakusho Co., Ltd. ACM-5LVT) under the conditions of liquid temperature 30°C and vacuum drawing. As a result, a coating liquid for forming a base layer was obtained, which contained 5 mass % of aggregates (that is, specific aggregates) formed by a plurality of carbon nanotubes entangled with one another in the solid content. Next, the obtained coating liquid for forming the base layer was applied onto a cylindrical mold to form a coating film, and the coating film was baked at 380° C. to form a seamless belt-like base layer having a thickness of 80 μm.
[0159] (Formation of elastic layer) Butyl acetate and carbon nanotubes (Showa Denko K.K.) were mixed in a mass ratio of 85:15 to prepare a dispersion (hereinafter also referred to as "CNT 15% dispersion"). The obtained dispersion was subjected to high-pressure dispersion treatment (conditions: liquid temperature 45°C, 50 MPa, number of valve passes (number of passes): 3) using a high-pressure homogenizer (HC3, Sanmaru Machinery Co., Ltd.). Next, 50 parts by mass of silicone rubber stock solution (X-34-1053 manufactured by Shin-Etsu Chemical Co., Ltd., solid content concentration: 60% by mass, solvent: butyl acetate) was added to 50 parts by mass of the dispersion liquid after the high pressure dispersion treatment to prepare a precursor liquid. The obtained precursor liquid was stirred for 10 minutes in a planetary mixer (ACM-5LVT manufactured by Aikosha Seisakusho Co., Ltd.) under the conditions of liquid temperature 30°C and vacuum drawing. As a result, a coating liquid for forming an elastic layer was obtained, which contained 20 mass % of aggregates (that is, specific aggregates) in the solid content, in which a plurality of carbon nanotubes were entangled with one another. Next, the obtained coating liquid for forming an elastic layer was applied onto the substrate layer to form a coating film, and the coating film was heated at 100° C. for 30 minutes to form an elastic layer with a thickness of 450 μm.
[0160] (Formation of release layer) A PFA tube (manufactured by Gunze Ltd.) having a thickness of 35 μm was placed on the elastic layer and heated at 200° C. for 120 minutes to form a release layer made of a fluororesin tube.
[0161] Through the above steps, a fixing belt was obtained.
[0162] <Examples 2 to 5> A fixing belt was produced in the same manner as in Example 1, except that the methods for forming the base layer and the elastic layer were changed to the following methods. That is, in forming the base layer of Example 1, the base layer was formed in the same manner as in Example 1, except that the number of passes of the high-pressure dispersion treatment of the 5% CNT dispersion liquid and the stirring time of the precursor liquid using a planetary mixer were appropriately changed as follows. Example 2: 3 passes of high-pressure dispersion treatment of 5% CNT dispersion, 40 minutes of mixing time with planetary mixer for precursor liquid Example 3: 8 passes of high-pressure dispersion treatment of 5% CNT dispersion, 10 minutes of mixing time with planetary mixer for precursor liquid Example 4: 5 passes of high-pressure dispersion treatment of 5% CNT dispersion, 15 minutes of mixing time with planetary mixer for precursor liquid Example 5: 5 passes of high-pressure dispersion treatment of 5% CNT dispersion, 15 minutes of mixing time with planetary mixer for precursor liquid
[0163] In addition, in forming the elastic layer in Example 1, the elastic layer was formed in the same manner as in Example 1, except that the number of passes of the high-pressure dispersion treatment of the 15% CNT dispersion liquid and the stirring time of the precursor liquid using a planetary mixer were appropriately changed as follows. Example 2: 3 passes of high pressure dispersion treatment of 15% CNT dispersion, 10 minutes mixing time of precursor liquid using planetary mixer Example 3: 3 passes of high pressure dispersion treatment of 15% CNT dispersion, 10 minutes mixing time of precursor liquid using planetary mixer Example 4: High-pressure dispersion treatment of 15% CNT dispersion liquid was performed twice, and the precursor liquid was mixed with a planetary mixer for 60 minutes. Example 5: 3 passes of high pressure dispersion treatment for 15% CNT dispersion, 8 minutes mixing time for precursor liquid using planetary mixer
[0164] <Examples 6 to 10> A fixing belt was produced in the same manner as in Example 1, except that the methods for forming the base layer and the elastic layer were changed to the following methods. That is, in forming the base layer of Example 1, the elastic layer was formed in the same manner as in Example 1, except that the amount of the 5% CNT dispersion liquid after the high-pressure dispersion treatment and the amount of the polyamic acid solution were appropriately changed as follows: Example 6: 1 part by mass of 5% CNT dispersion after high-pressure dispersion treatment, 280 parts by mass of polyamic acid solution Example 7: 100 parts by mass of 5% CNT dispersion after high-pressure dispersion treatment, 250 parts by mass of polyamic acid solution Example 8: 1 part by mass of 5% CNT dispersion after high-pressure dispersion treatment, 280 parts by mass of polyamic acid solution Example 9: 100 parts by mass of 5% CNT dispersion after high-pressure dispersion treatment, 111.1 parts by mass of polyamic acid solution Example 10: 100 parts by mass of 5% CNT dispersion after high-pressure dispersion treatment, 98.5 parts by mass of polyamic acid solution
[0165] In addition, in forming the elastic layer of Example 1, the elastic layer was formed in the same manner as in Example 1, except that the amount of the 15% CNT dispersion after the high-pressure dispersion treatment and the amount of the silicone rubber stock solution were appropriately changed as follows. Example 6: 0.4 parts by mass of 15% CNT dispersion after high-pressure dispersion treatment, 99.6 parts by mass of silicone rubber stock solution Example 7: 0.4 parts by mass of 15% CNT dispersion after high-pressure dispersion treatment, 99.6 parts by mass of silicone rubber stock solution Example 8: 50 parts by mass of 15% CNT dispersion after high-pressure dispersion treatment, 50 parts by mass of silicone rubber stock solution Example 9: 72.8 parts by mass of 15% CNT dispersion after high-pressure dispersion treatment, 27.3 parts by mass of silicone rubber stock solution Example 10: 76.58 parts by mass of 15% CNT dispersion after high-pressure dispersion treatment, 23.4 parts by mass of silicone rubber stock solution
[0166] <Examples 11 to 17> A fixing belt was produced in the same manner as in Example 1, except that the methods for forming the base layer and the elastic layer were changed to the following methods. That is, in forming the base layer in Example 1, a precursor liquid was prepared in which the amount of 5% CNT dispersion after high-pressure dispersion treatment and the amount of polyamic acid solution were appropriately set as shown below, and then the precursor liquid was stirred with a planetary mixer, and the 5% CNT dispersion used in Example 1 was added in the amount shown below. The base layer was formed in the same manner as in Example 1, except that a coating liquid was used that had been further stirred with the planetary mixer under the conditions of a liquid temperature of 30°C and normal pressure for 1 minute. Example 11: 100 parts by mass of 5% CNT dispersion after high-pressure dispersion treatment, 704 parts by mass of polyamic acid solution, 33.3 parts by mass of 5% CNT dispersion Example 12: 33.3 parts by mass of 5% CNT dispersion after high-pressure dispersion treatment, 704 parts by mass of polyamic acid solution, 100 parts by mass of 5% CNT dispersion Example 13: 66.6 parts by mass of 5% CNT dispersion after high-pressure dispersion treatment, 704 parts by mass of polyamic acid solution, 66.6 parts by mass of 5% CNT dispersion Example 14: 126.6 parts by mass of 5% CNT dispersion after high-pressure dispersion treatment, 704 parts by mass of polyamic acid solution, 6.6 parts by mass of 5% CNT dispersion Example 15: 100 parts by mass of 5% CNT dispersion after high-pressure dispersion treatment, 704 parts by mass of polyamic acid solution, 33.3 parts by mass of 5% CNT dispersion Example 16: 100 parts by mass of 5% CNT dispersion after high-pressure dispersion treatment, 704 parts by mass of polyamic acid solution, 33.3 parts by mass of 5% CNT dispersion Example 17: 100 parts by mass of 5% CNT dispersion after high-pressure dispersion treatment, 704 parts by mass of polyamic acid solution, 33.3 parts by mass of 5% CNT dispersion
[0167] In addition, in forming the elastic layer in Example 1, a precursor liquid was prepared by appropriately adjusting the amount of the 15% CNT dispersion after the high-pressure dispersion treatment and the amount of the silicone rubber stock liquid as shown below. Next, the precursor liquid was stirred with a planetary mixer, and then the 15% CNT dispersion used in Example 1 was added in the amount shown below. The elastic layer was formed in the same manner as in Example 1, except that a coating liquid was used that had been further stirred with the planetary mixer for 1 minute under the conditions of a liquid temperature of 30°C and normal pressure. Example 11: 33.15 parts by mass of 15% CNT dispersion after high-pressure dispersion treatment, 65 parts by mass of silicone rubber stock solution, 1.48 parts by mass of 15% CNT dispersion Example 12: 33.15 parts by mass of 15% CNT dispersion after high-pressure dispersion treatment, 65 parts by mass of silicone rubber stock solution, 1.48 parts by mass of 15% CNT dispersion Example 13: 33.15 parts by mass of 15% CNT dispersion after high-pressure dispersion treatment, 65 parts by mass of silicone rubber stock solution, 1.48 parts by mass of 15% CNT dispersion Example 14: 33.15 parts by mass of 15% CNT dispersion after high-pressure dispersion treatment, 65 parts by mass of silicone rubber stock solution, 1.48 parts by mass of 15% CNT dispersion Example 15: 1.48 parts by mass of 15% CNT dispersion after high-pressure dispersion treatment, 65 parts by mass of silicone rubber stock solution, 33.15 parts by mass of 15% CNT dispersion Example 16: 21.2 parts by mass of 15% CNT dispersion after high-pressure dispersion treatment, 65 parts by mass of silicone rubber stock solution, 1.42 parts by mass of 15% CNT dispersion Example 17: 43.45 parts by mass of 15% CNT dispersion after high-pressure dispersion treatment, 65 parts by mass of silicone rubber stock solution, 1.51 parts by mass of 15% CNT dispersion
[0168] <Comparative Example 1> A fixing belt was produced in the same manner as in Example 1, except that the methods for forming the base layer and the elastic layer were changed as follows.
[0169] (Formation of base layer) That is, the dispersion liquid (CNT 5% dispersion liquid) used in forming the base layer in Example 1 that was not subjected to high pressure dispersion treatment was used, and 250 parts by mass of a polyamic acid solution (TX-HMM (polyimide varnish) manufactured by Unitika Ltd., solid content concentration: 18% by mass, solvent: NMP) was added to 100 parts by mass of the dispersion liquid, and mixed with a planetary mixer (conditions: liquid temperature 30°C, 1 minute) to obtain a coating liquid for forming a base layer. A base layer was formed in the same manner as in Example 1, except that this coating liquid for forming a base layer was used.
[0170] (Formation of elastic layer) That is, the dispersion liquid (CNT 15% dispersion liquid) used in forming the elastic layer in Example 1 that was not subjected to high pressure dispersion treatment was used, and 50 parts by mass of silicone rubber stock solution (X-34-1053 manufactured by Shin-Etsu Chemical Co., Ltd., solid content concentration: 60% by mass, solvent: butyl acetate) was added to 50 parts by mass of the dispersion liquid, and mixed with a planetary mixer (conditions: liquid temperature 30°C, 1 minute) to obtain a coating liquid for forming an elastic layer. An elastic layer was formed on a substrate layer in the same manner as in Example 1, except that this coating liquid for forming an elastic layer was used.
[0171] <Comparative Example 2> A fixing belt was produced in the same manner as in Example 1, except that the methods for forming the base layer and the elastic layer were changed as follows.
[0172] (Formation of base layer) A base layer was formed in the same manner as in Example 1, except that a polyamic acid solution (TX-HMM (polyimide varnish) manufactured by Unitika Ltd.) was used as it was as the coating liquid for forming the base layer.
[0173] (Formation of elastic layer) An elastic layer was formed on a base layer in the same manner as in Example 1, except that a silicone rubber stock solution (X-34-1053 manufactured by Shin-Etsu Chemical Co., Ltd.) was used as it was as a coating solution for forming an elastic layer.
[0174] <Comparative Example 3> A fixing belt was produced in the same manner as in Example 1, except that the methods for forming the base layer and the elastic layer were changed as follows.
[0175] (Formation of base layer) A precursor liquid was prepared by adding 250 parts by mass of a polyamic acid solution (TX-HMM (polyimide varnish) manufactured by Unitika Ltd., solid content concentration: 18% by mass, solvent: NMP) to 100 parts by mass of the dispersion liquid after the high-pressure dispersion treatment obtained in the formation of the base layer in Example 1. The obtained precursor liquid was stirred for 70 minutes in a planetary mixer (ACM-5LVT manufactured by Aikosha Seisakusho Co., Ltd.) under conditions of a liquid temperature of 30°C and vacuum drawing. As a result, a coating liquid for forming a base layer was obtained, which contained 10 mass % of aggregates (that is, specific aggregates) formed by a plurality of carbon nanotubes entangled with one another in the solid content. Next, the obtained coating liquid for forming the base layer was applied onto a cylindrical mold to form a coating film, and the coating film was baked at 380° C. to form a seamless belt-like base layer having a thickness of 80 μm.
[0176] (Formation of elastic layer) That is, a precursor liquid was prepared by adding 60 parts by mass of silicone rubber stock solution (X-34-1053 manufactured by Shin-Etsu Chemical Co., Ltd., solid content concentration: 60% by mass, solvent: butyl acetate) to 50 parts by mass of the dispersion liquid after the high-pressure dispersion treatment obtained in the formation of the elastic layer in Example 1. The obtained precursor liquid was stirred for 80 minutes in a planetary mixer (ACM-5LVT manufactured by Aikosha Seisakusho Co., Ltd.) under the conditions of liquid temperature 30°C and vacuum drawing. In this manner, a coating liquid for forming an elastic layer was obtained, which contained 20 mass % of aggregates (that is, specific aggregates) formed by a plurality of carbon nanotubes entangled with one another in the solid content. Next, the obtained coating liquid for forming an elastic layer was applied onto the substrate layer to form a coating film, and the coating film was heated at 100° C. for 30 minutes to form an elastic layer with a thickness of 450 μm.
[0177] <Evaluation of durability of fixing belt> The fixing belt obtained in each example was attached to the fixing device of an image forming apparatus (Versant 3100i Press manufactured by Fuji Xerox Co., Ltd.) that employs a fixing method in which a heat source is present inside the fixing belt and heat from the heat source is transmitted to the toner image via the fixing belt. Using this image forming apparatus, halftone images with a Cin of 50% were continuously output on A4 paper (P paper manufactured by Fujifilm Business Innovation Co., Ltd.) at an output speed (printing speed) of 100 ppm (100 sheets per minute). After every 100,000 sheets printed, the presence or absence of image defects caused by wrinkles in the release layer was checked, and the number of sheets output until the fixing belt broke and the device stopped running (the device stopped) was confirmed to evaluate the durability (i.e., lifespan) of the fixing belt. Here, wrinkles in the release layer occur due to a gradual increase in the sliding resistance between the belt and the driving member (i.e., an increase in torque), and are one of the factors that cause belt breakage. Therefore, even if printing is continued, the slower the occurrence of image defects due to wrinkles in the release layer, the more excellent the durability of the fixing belt is.
[0178] The durability of the fixing belt was evaluated according to the following criteria. -Image defect- A(◎): No image defects occurred at 300,000 copies. B (Good): No image defects occurred at 200,000 copies, but image defects were confirmed at 300,000 copies. C (△): No image defects occurred at 100,000 copies, but image defects were confirmed at 200,000 copies. D(x): Image defects were confirmed at the 100,000th sheet mark.
[0179] -Belt broken- A (◎): No breakage of the fixing belt was observed (the running did not stop) up to 300,000 sheets. B (◯): Breakage of the fixing belt was observed when printing between 200,000 and 300,000 sheets. C (△): Breakage of the fixing belt was observed when printing 100,000 or more but less than 200,000 copies. D(x): The fixing belt broke when printing less than 100,000 sheets.
[0180] [Table 1]
[0181] From the above results, it is apparent that the fixing belt of this embodiment has higher durability and a longer life than the fixing belt of the comparative example. [Explanation of symbols]
[0182] 80 Fixing device 82 Sliding member 84 Heating Belt 86 Fuser Belt Module 88 Pressure Roll 89A halogen heater 89 Heated pressure roll 90A halogen heater 90 Support Roll 92A halogen heater 92 Support Roll 94 Posture Correction Roll 96 Support member 98 Support Roll 100 Image forming device 110 Fixing belt 110A base material 110B Elastic layer 110C Release layer
Claims
1. The sheet has a base layer including a resin, an elastic layer including an elastic material, and a release layer in this order, The base material layer and the elastic layer each further include an aggregate formed by a plurality of fibrous carbons entangled with each other, the maximum diameter of the aggregate in the base layer is 8.75% or more and 40% or less of the thickness of the base layer, a ratio of a minor axis Y to a major axis X of the aggregate in the base layer (minor axis Y / major axis X) is 0.1 or more and 1 or less; a maximum diameter of the aggregate in the elastic layer is 1.55% or more and 13.3% or less of a thickness of the elastic layer, a ratio of a minor axis Y to a major axis X of the aggregate in the elastic layer (minor axis Y / major axis X) is 0.1 or more and 1 or less.
2. 2. The fixing belt according to claim 1, wherein the base layer and the elastic layer each further comprise non-entangled fibrous carbon.
3. 3. The fixing belt according to claim 2, wherein the content A of the aggregates and the content B of the non-entangled fibrous carbon in the base material layer and the elastic layer respectively satisfy a relationship of A≧B on a mass basis.
4. 4. The fixing belt according to claim 2, wherein the base material layer and the elastic layer each have a ratio (A / (A+B)) of the content A of the aggregates to a total amount of the content A of the aggregates and the content B of the unentangled fibrous carbon, the ratio being 0.50 or more and 0.95 or less, on a mass basis.
5. The fixing belt according to any one of claims 1 to 4, wherein a content A1 of the aggregate contained in the base layer is 0.1 mass % or more and 20 mass % or less with respect to a total mass of the base layer.
6. 6. The fixing belt according to claim 1, wherein the content A2 of the aggregate contained in the elastic layer is 0.1% by mass or more and 40% by mass or less with respect to the total mass of the elastic layer.
7. The fixing belt according to any one of claims 1 to 4, wherein a content A1 of the aggregate contained in the base material layer and a total mass A2 of the aggregate contained in the elastic layer satisfy a relationship of A1≦A2 on a mass basis.
8. 8. The fixing belt according to claim 7, wherein the content A1 of the aggregate is 0.1 mass % or more and 20 mass % or less with respect to the total mass of the base material layer, and the content A2 of the aggregate is 0.1 mass % or more and 40 mass % or less with respect to the total mass of the elastic layer.
9. 9. The fixing belt according to claim 1, wherein the fibrous carbon is a carbon nanotube.
10. A pressure-sensitive adhesive sheet comprising a base layer containing a resin, an elastic layer containing an elastic material, and a release layer in this order, The base material layer and the elastic layer each further include an aggregate formed by a plurality of fibrous carbons entangled with each other, the maximum diameter of the aggregate in the base layer is 8.75% or more and 40% or less of the thickness of the base layer, a maximum diameter of the aggregate in the elastic layer is 1.55% or more and 13.3% or less of a thickness of the elastic layer, The base material layer and the elastic layer each further contain fibrous carbon that is not entangled with each other, a content A of the aggregates in the base material layer and a content B of the non-entangled fibrous carbon in the elastic layer, each of which satisfies a relationship of A≧B on a mass basis.
11. A pressure-sensitive adhesive sheet comprising a base layer containing a resin, an elastic layer containing an elastic material, and a release layer in this order, The base material layer and the elastic layer each further include an aggregate formed by a plurality of fibrous carbons entangled with each other, the maximum diameter of the aggregate in the base layer is 8.75% or more and 40% or less of the thickness of the base layer, a maximum diameter of the aggregate in the elastic layer is 1.55% or more and 13.3% or less of a thickness of the elastic layer, The base material layer and the elastic layer each further contain fibrous carbon that is not entangled with each other, the base material layer and the elastic layer each have a ratio (A / (A+B)) of the content A of the aggregate to the total amount of the content A of the aggregate and the content B of the fibrous carbon that is not entangled with each other, of 0.50 or more and 0.95 or less, on a mass basis.
12. A pressure-sensitive adhesive sheet comprising a base layer containing a resin, an elastic layer containing an elastic material, and a release layer in this order, The base material layer and the elastic layer each further include an aggregate formed by a plurality of fibrous carbons entangled with each other, the maximum diameter of the aggregate in the base layer is 8.75% or more and 40% or less of the thickness of the base layer, a maximum diameter of the aggregate in the elastic layer is 1.55% or more and 13.3% or less of a thickness of the elastic layer, A fixing belt, wherein a content A1 of the aggregate contained in the base layer is 0.1% by mass or more and 20% by mass or less with respect to a total mass of the base layer.
13. A pressure-sensitive adhesive sheet comprising a base layer containing a resin, an elastic layer containing an elastic material, and a release layer in this order, The base material layer and the elastic layer each further include an aggregate formed by a plurality of fibrous carbons entangled with each other, the maximum diameter of the aggregate in the base layer is 8.75% or more and 40% or less of the thickness of the base layer, a maximum diameter of the aggregate in the elastic layer is 1.55% or more and 13.3% or less of a thickness of the elastic layer, A fixing belt, wherein a content A2 of the aggregate contained in the elastic layer is 0.1% by mass or more and 40% by mass or less with respect to a total mass of the elastic layer.
14. A pressure-sensitive adhesive sheet comprising a base layer containing a resin, an elastic layer containing an elastic material, and a release layer in this order, The base material layer and the elastic layer each further include an aggregate formed by a plurality of fibrous carbons entangled with each other, the maximum diameter of the aggregate in the base layer is 8.75% or more and 40% or less of the thickness of the base layer, a maximum diameter of the aggregate in the elastic layer is 1.55% or more and 13.3% or less of a thickness of the elastic layer, A fixing belt, wherein a content A1 of the aggregate contained in the base layer and a total mass A2 of the aggregate contained in the elastic layer satisfy a relationship of A1≦A2 on a mass basis.
15. A pressure-sensitive adhesive sheet comprising a base layer containing a resin, an elastic layer containing an elastic material, and a release layer in this order, The base material layer and the elastic layer each further include an aggregate formed by a plurality of fibrous carbons entangled with each other, the maximum diameter of the aggregate in the base layer is 8.75% or more and 40% or less of the thickness of the base layer, a maximum diameter of the aggregate in the elastic layer is 1.55% or more and 13.3% or less of a thickness of the elastic layer, a content A1 of the aggregate contained in the base layer and a total mass A2 of the aggregate contained in the elastic layer satisfy a relationship of A1≦A2 on a mass basis, a content A1 of the aggregate is 0.1 mass % or more and 20 mass % or less with respect to the total mass of the base material layer, and a content A2 of the aggregate is 0.1 mass % or more and 40 mass % or less with respect to the total mass of the elastic layer.
16. A pressure-sensitive adhesive sheet comprising a base layer containing a resin, an elastic layer containing an elastic material, and a release layer in this order, The base material layer and the elastic layer each further include an aggregate formed by a plurality of fibrous carbons entangled with each other, the maximum diameter of the aggregate in the base layer is 8.75% or more and 40% or less of the thickness of the base layer, a maximum diameter of the aggregate in the elastic layer is 1.55% or more and 13.3% or less of a thickness of the elastic layer, The fuser belt, wherein the fibrous carbon is a carbon nanotube.
17. A first rotating body and a second rotating body arranged in contact with an outer surface of the first rotating body, At least one of the first rotating body and the second rotating body is the fixing belt according to any one of claims 1 to 16, a fixing device for fixing a toner image formed on a surface of the recording medium by inserting the recording medium through a contact portion between the first rotating body and the second rotating body;
18. An image carrier; a charging means for charging the surface of the image carrier; an electrostatic latent image forming means for forming an electrostatic latent image on the charged surface of the image carrier; a developing unit for developing the electrostatic latent image formed on the surface of the image carrier with a developer containing a toner to form a toner image; a transfer means for transferring the toner image onto a surface of a recording medium; A fixing unit that fixes the toner image onto the recording medium, the fixing unit being configured as claimed in claim 17; An image forming apparatus comprising:
Citation Information
Patent Citations
Method of manufacturing carbon nanotube structure as well as carbon nanotube structure and carbon nanotube device using the same
JP2002346996A
Fixing roller
JP2005292218A
Composite fixing belt and its manufacturing method
JP2006199026A
Heat fixing member and heat fixing apparatus
JP2006259712A
Elastic composition, fixing roller, method for producing fixing roller, fixing apparatus and image-forming apparatus
JP2007332281A